Neuromodulatory nerve regeneration: Adipose tissue‐derived stem cells and neurotrophic mediation in peripheral nerve regeneration. Issue 12 (16th September 2013) - Widgerow, Alan D.; Salibian, Ara A.; Lalezari, Shadi; Evans, Gregory R.D.
<x xml:space="preserve">Abstract</x> Peripheral nerve injury requiring nerve gap reconstruction remains a major problem. In the quest to find an alternative to autogenous nerve graft procedures, attempts have been made to differentiate mesenchymal stem cells into neuronal lineages in vitro and utilize these cellular constructs for nerve regeneration. Unfortunately, this has produced mixed results, with no definitive procedure matching or surpassing traditional nerve grafting procedures. This review presents a different approach to nerve regeneration. The literature was reviewed to evaluate current methods of using adipose‐derived stem cells (ADSCs) for peripheral nerve regeneration in in vivo models of animal peripheral nerve injury. The authors present cited evidence for directing nerve regeneration through paracrine effects of ADSCs rather than through in vitro nerve regeneration. The paracrine effects rely mainly, but not solely, on the elaboration of nerve growth factors and neurotrophic mediators that influence surrounding host cells to orchestrate in vivo nerve regeneration. Although this paradigm has been indirectly referred to in a host of publications, few major efforts for this type of neuromodulatory nerve regeneration have been forthcoming. The ADSCs are initially "primed" in vitro using specialized controlled medium (not for neuronal differentiation but for sustainability) and then incorporated into a hydrogel base matrix designed for this purpose. This core matrix is then introduced into a natural collagen‐based nerve conduit. The prototype design concepts, evidence for paracrine influences, and regulatory hurdles that are avoided using this approach are discussed. © 2013 Wiley Periodicals, Inc.